2006
DOI: 10.1073/pnas.0510997103
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell factor receptor induces progenitor and natural killer cell-mediated cardiac survival and repair after myocardial infarction

Abstract: Inappropriate cardiac remodeling and repair after myocardial infarction (MI) predisposes to heart failure. Studies have reported on the potential for lineage negative, steel factor positive (c-kit ؉ ) bone marrow-derived hematopoetic stem͞progenitor cells (HSPCs) to repair damaged myocardium through neovascularization and myogenesis. However, the precise contribution of the c-kit signaling pathway to the cardiac repair process has yet to be determined. In this study, we sought to directly elucidate the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 36 publications
2
87
0
1
Order By: Relevance
“…The current study demonstrated that CXCR4 overexpressing MSCs increase the expression of ckit. This is of potential importance because c-kit positive cells play a significant contributing role in cardiac repair and restoration of heart function after myocardial infarction [24]. The significance of the increased number of c-kit positive cells further underscores the factor that c-kit deficient cardiac progenitor cells in W/W v mice prevent cell differentiation during aging or after injury [24] and that c-kit positive cells are also associated with enhanced angiogenesis [25].…”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrated that CXCR4 overexpressing MSCs increase the expression of ckit. This is of potential importance because c-kit positive cells play a significant contributing role in cardiac repair and restoration of heart function after myocardial infarction [24]. The significance of the increased number of c-kit positive cells further underscores the factor that c-kit deficient cardiac progenitor cells in W/W v mice prevent cell differentiation during aging or after injury [24] and that c-kit positive cells are also associated with enhanced angiogenesis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about inhibiting KIT were raised recently by studies of the Kit W/W-v mouse, a compound heterozygote in which one allele is deleted and the other has reduced kinase activity. This mouse, when subjected to myocardial infarction, had markedly impaired postmyocardial infarction repair and survival, which was attributed to failure to recruit bone-marrow-derived stem/progenitor cells that are pro-angiogenic to the infarct zone 89,90 . This raises concerns that inhibition of KIT might aggravate pathological remodelling of the heart postmyocardial infarction and prevent repair.…”
Section: Sorafenibmentioning
confidence: 99%
“…Our data demonstrate that the absence of cardiac-infiltrating lymphoid cells is associated with a poorer outcome. Previous publications underlined the importance of NK cell dependence in heart recovery following MI (17). In their study, Ayach and coworkers (17) showed that specific NK cell depletion in immune-competent mice reduced their survival by 30% as a result of heart failure.…”
Section: Discussionmentioning
confidence: 98%
“…It is an inhibitor of IL-1, IL-6, IL-8, and TNF-a production and has been reported to modulate the function and phenotype of monocytes/macrophages (15,16). In a recent study, it was shown that c-kit-mediated mobilization of bone marrow NK cells rescues hearts post-myocardial infarction (MI), contributing to improved remodeling and cardiac function (17). The literature is, however, missing the precise mechanism of NK cellmediated cardiac repair following infarction.…”
mentioning
confidence: 99%